Creative content on the digital campaign Tokopedia “Seller Story” - Rozalena, Agustin (Penerbit Universiti Kebangsaan Malaysia, 2020)
Tokopedia is an e-commerce with the largest number of monthly web visitors in the third quarter of 2019. This study is to analyze the creative content of the digital campaign Tokopedia Seller Story series. This study aim to (1) describe the characteristics of digital campaigns through the video series seller story; (2) analyze discourse framed through digital campaigns. The methodology is descriptive qualitative with the paradigm of framing analysis by Robert N. Entman Model. Researchers use depth interviewing techniques, Focus Group Discussion (FGD), observation, and document to obtain data from predetermined informants. The subjects of this study were three video seller stories of Tokopedia seller story. Researchers used document analysis with data analysis techniques used in the framing analysis. Framing analysis research is interesting to study when the information translates into audiovisual or video. The results found, (1) The content creation of the digital campaign is the persuasion of the company to customers through the "All Begins from Tokopedia" and "MulaiAjaDulu" hashtag. (2) Seller story impressions related to Tokopedia's economic interests as a platform. Based on analysis and interpretation of framing, researchers found a discourse built to strengthen customer perception and awareness in choosing Tokopedia as an empathetic and inspirational platform and stated Tokopedia had helped new entrepreneurs succeed.